The relationship between uric acid and total femur bone mineral density in hypertensive and non-hypertensive populations - Su, Yingjie; Ding, Ning; Zhou, Yang; Yang, Guifang; Chai, Xiangping (Frontiers in Endocrinology, 2022)
Objective: This study aimed to explore the association between uric acid (UA) and total femur bone mineral density (BMD) in hypertensive and non-hypertensive groups. Methods: We conducted a cross-sectional study of 13,108 participants in the NHANES database, including 4,679 hypertensive and 8,429 non-hypertensive subjects. A weighted multiple linear regression analysis was conducted to explore the association between UA and total femur BMD. Results: In the hypertensive group, the relationship between UA and total femur BMD was positive (β, 3.02 [95%CI, -0.44, 6.48], p=0.0962). In the non-hypertensive group, the association was significantly positive (β, 5.64 [95%CI, 2.06, 9.22], p=0.0038). In gender-stratified analysis, UA was analyzed as a continuous variable and a categorical variable (quartile). The significantly positive association was present in both hypertensive male group (β, 5.10 [95%CI, 0.98, 9.21], p for trend=0.0042) and non-hypertensive male group(β, 10.63 [95%CI, 6.32, 14.94], p for trend=0.0001). A smooth curve fitting showed that in the hypertensive male group, the relationship between UA and total femur BMD was an inverted U-shaped curve. In the hypertensive female group, the relationship was basically negative. In the non-hypertensive population, the relationship between UA and total femur BMD was an inverted U curve in both males and females. Conclusion: In the hypertensive male group, the association between UA and total femur BMD was an inverted U-shaped curve. As to females, the relationship was basically negative. In the non-hypertensive group, the association between UA and total femur BMD was an inverted U-shaped curve in different genders.